Profit based unit commitment problem solution using metaheuristic optimisation approach. Issue 1 (31st December 2023) - Kumar, V.; Naresh, R.; Sharma, Veena
Abstract : Earlier power utilities had generated electrical power with the goal of minimising the costs and meeting both demand and reserves. Generation companies (GENCOs) schedule their generators under a new structure to maximise the profit. This paper provides a computational methodology based on monarch butterfly optimisation (MBO) to find a solution to the problem of profit-based unit commitment (PBUC), taking into account the power and reserve conditions. The proposed method allows GENCOs to determine how much power and reserve should be sold in the markets in order to achieve maximum profit. The binary variables of unit commitment problems are handled by modifying the continuous-time nature of the monarch butterfly algorithm. The computational approach maximises the profit but also handles the mixed constraints of the commitment problem. The effect of thermal turbine valve point loading is also taken into consideration. The computational technique has been used to solve two test systems in the absence and presence of steam turbine valve point loading effects. The results obtained are in agreement with the recent results available in the literature. Comparative analysis shows the effectiveness of the proposed MBO based solution methodology in terms of profit earned and execution time in relation to other techniques.